PENGARUH INFRASTRUKTUR DAN PENDIDIKAN TERHADAP KEMISKINAN DAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI BALI - Sila Putra, I Ketut Adi Winanda; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Community welfare is measured using a composite indicator called the Human Development Index (HDI). This level of human development largely determines the ability of the population to absorb and manage the sources of economic growth. The purpose of this study was to analyze the effect of infrastructure and education on poverty and community welfare in the Regency / City of Bali Province. The data used are secondary data with path analysis techniques. Based on the analysis, it was found that infrastructure and education had a significant negative effect on poverty in the regencies / cities of Bali Province. Infrastructure has no effect on Community Welfare, while education has a significant positive effect on Community Welfare in the Regency / City of Bali Province. Poverty reduction has no effect on Community Welfare in the Regency / City of Bali Province. There is no indirect effect of infrastructure and education on community welfare through poverty in the regencies / cities of Bali province.   Keywords: IPM, poverty, infrastructure, education